PERANCANGAN SISTEM INFORMASI PELAYANAN JASA LAUNDRY BERBASIS WEB PADA DIAN LAUNDRY - Bobby Perdana, - (2018)
This study was conducted the need for faster and easier services for service and computer media. This service can also put a lot of information you want to do in the community. Information where that can be done easily and quickly Obtained by consumer information. The purpose of this research is to make the right information system and efficient, very important to support service to consumer. To achieve this goal the authors conducted research with research methods are: direct observation, interviews, literature, and methods of analysis and system design. The system is designed using UML modeling, while the programming languages are PHP and MySQL databases. The result of the design of this system is the information system that provides input and output data, and data on consumers of the information available